Pendampingan Teknis Pemasangan Sambungan Rumah di Desa Kopeng Kecamatan Getasan Kabupaten Semarang - Haji, Son; Setyaningsih, Anggih; Wahyuni, Thalia Erna (Jurnal Pengabdian KOLABORATIF, 2025)
Technical assistance for installing house connections (SR) in Kopeng Village, Getasan District, Semarang Regency, faces a number of challenges and opportunities that can be analyzed from several aspects. Kopeng Village is an area where most of the population depends on clean water from natural sources. However, direct access to clean water through the distribution network is still limited in some areas. The research methods used include: the research approach used in this research is qualitative and quantitative, data collection techniques to obtain accurate and relevant data, data analysis techniques, data evaluation, and validation. The research results were evaluated by comparing findings in the field with literature related to clean water management and local government policies. Thus, this program not only improves the quality of life of residents but also builds independence in managing water resources. However, there are several obstacles that still need to be considered, such as budget limitations in reaching more homes and the need for ongoing education so that people can independently maintain their home connections. Therefore, program sustainability is an important factor in ensuring long-term benefits from this activity.